Spermatogenesis of riffle bugs, Rhagovelia whitei and Rhagovelia sp (Veliidae), and backswimmers Martarega sp (Notonectidae). - Castanhole, M. M.; Pereira, L. L.; de Souza, H. V.; Itoyama, M. M. (My University, 2012)
We examined the course of spermatogenesis and the meiotic chromosome complements in aquatic species of true bugs, Heteroptera. The chromosome complement of the Veliidae species was 2n = 39 (38A + X0) and 23 (22A + X0) in Rhagovelia whitei and Rhagovelia sp, respectively, and in the species of the Notonectidae (Martarega sp) it was 26 (22A + 2m + XY); all collected from the region of São José do Rio Preto, SP, Brazil. An impressive characteristic of the first analysis was the size of the cells belonging to Martarega sp, which were six times larger than the same cells in Pentatomidae and twice as large as the cells in aquatic Heteroptera (Gerridae). Regarding spermatogenesis, all the species analyzed showed the same pattern: holocentric chromosomes and elongated spermatids with the chromatin distributed evenly along the head. The family Veliidae showed several bodies impregnated with silver nitrate at prophase, while the family Notonectidae displayed only one. The cells of Notonectidae also showed an evident and round body until the end of prophase I and in the family Veliidae the silver-impregnated bodies were disorganized, where the only region visualized was possibly that of the NOR. In metaphase, silver-stained regions were found at the periphery of all chromosomes in Veliidae and at the periphery of some chromosomes in Notonectidae. The spermatids of Veliidae showed a less silver-impregnated vesicle, while Notonectidae showed silver staining only in part of the nuclear membrane. Therefore, families of Heteroptera have some differences and features that can help identify and classify these species.
Keywords: silver nitrate; animal; cytology; Heteroptera; male; metabolism; nucleolus; physiology; spermatogenesis; staining; testis; Animals; Cell Nucleolus; Male; Silver Nitrate; Spermatogenesis; Staining and Labeling; Testis